Jewish high society in Old Regime Berlin - Hertz, Deborah Sadie (Yale University Press, 1988)
During the quarter century between 1780 and 1806, Berlin's courtly and intellectual elites gathered in the homes of a few wealthy, cultivated Jewish women to discuss the events of the day. Princes, nobles, upwardly mobile writers, actors, and beautiful Jewish women flocked to the salons of Rahel Varnhagen, Henriette Herz, and Dorothea von Courland, creating both a new cultural institution and an example of social mixing unprecedented in the German past. In this book, Deborah Hertz offers the first detailed history of these salons, using rich narrative as well as analytic social history to explain why such an institution arose and what it meant to those involved. Hertz reconstructs the cultural and social context that nurtured salon life, describing how the salons emerged out of courtly society, commercial leisure institutions, and the city's new intellectual clubs. Using a collective biography of one hundred participants in sixteen salons, Hertz shows that there were complex social and personal motives for salon participation. Noblemen, for example, needed Jewish financiers for private loans, but they also wanted access to more progressive cultural currents. For Jewish women, salon leadership offered not only an escape from a restricted home life but also social and personal power, power that was frequently consolidated in their upwardly mobile marriages to noblemen. However advantageous and stimulating these salons were for their participants, they were the product of a transitory convergence of social and cultural structures. Hertz concludes by exploring how both underground antisemitic gossip and the new patriotism unleashed by the upheavals in Prussia after 1806 destroyed Jewish salon life in Berlin.